An organic-inorganic hybrid perovskite with copper clusters: properties and prospects - Chaykun, Ksenia (2023)
Hybrid organo-inorganic perovskites are a well-known material in the field of optoelectronic devices. They are easy to synthesize and scale, and due to the variability of composition, their properties are tunable. Until now, a significant problem in the use of this material is the environmental instability. Changing the composition of the layers by introducing copper complexes in place of an organic layer can help reduce the material degradation rate, change the optical properties, as well as add one more degree of freedom in their variability. The structure and phase transitions of hybrid perovskite with copper paddle-wheel clusters linking perovskite layers [Cu(O2C-(CH2)3-NH3)2]PbBr4 were investigated using Raman spectroscopy under variable pressure up to 17 GPa, furthermore in the temperature range between 80 K to 373 K. The following optical properties of the material are described: photoluminescence, the dependence of absorption on pressure. Primary DFT calculations have shown that the studied material can be considered as a three-component system in which energy transfers between components are possible. Based on them, further prospects for the study and application of copper-containing perovskite are proposed.